Dampak Pemasaran Produk Melalui Live Streaming Terhadap Terbukannya Lapangan Pekerjaan Baru Pada Platform Linkedin - PUTRA, RIZKY FEBRIAN (Universitas Negeri Surabaya, 2024)
In today's digital era, all business activities are mostly carried out through online media. Likewise with methods for marketing products. Many companies or business actors have switched to marketing products through social media. One way is to take advantage of the live streaming feature on social media. With this phenomenon, it will have an impact on the opportunity to open new jobs in Indonesia. The ultimate goal of this study is to see whether the phenomenon of product marketing through live streaming can open up new jobs in Indonesia. After this research was conducted, it has been proven that the existence of product marketing through live streams can open up opportunities for new jobs on the Linkedin platform. Some of the vacancies available include Live streaming hosts, social media specialists, and live streaming operators. For live streaming hosts, there are five